KONTES KECANTIKAN DAN EKSPLOITASI PEREMPUAN DALAM MEDIA - Hermansyah Hermansyah (Marwah: Jurnal Perempuan, Agama dan Jender, 2011)
The beauty contest is a contest which covered and broadcasted by many of electronic and printed media, This social fenomena arises the questions, what is the goal of this contest ?, what are the requirements which must be fulfilled by the participant, what are the creteria of assesments, face beauty, ideal body size, or clothes weared by the participant ?. Is the intellectual factor including into assessment of creteria ? or are there any other requirements must be fulfilled by the participant?, why does media seems more enthusiastic to published and broadcasts this activity?. From all the questions, the writer wishes to analyse, is the taking part of women in this contest and the enthusiastic of media to published and broadcasts this activity is an exploitation of media toward woman? The analaysis showed that the international, national and local beauty contests is an exploitation of media toward woman.